2022
DOI: 10.3390/md20060399
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Virtual Screening of Marine Aldehyde Derivatives from Seaweeds against SARS-CoV-2

Abstract: Coronavirus disease 2019, caused by the outbreak of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is an ongoing global pandemic that poses an unprecedented threat to the global economy and human health. Several potent inhibitors targeting SARS-CoV-2 have been published; however, most of them have failed in clinical trials. This study aimed to assess the therapeutic compounds among aldehyde derivatives from seaweeds as potential SARS-CoV-2 inhibitors using a computer simulation protocol. The abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…A multitude of parameters were computed, including the two-dimensional Fast Polar Surface Area (2D_FPSA), Atom-based Log P98 ( A Log P 98), the integrity of the Blood–Brain Barrier (BBB), the presence and influence of Cytochrome P4502D6 (CYP2D6), and the propensity for Hepatotoxicity (HEPATOX). 54–56…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A multitude of parameters were computed, including the two-dimensional Fast Polar Surface Area (2D_FPSA), Atom-based Log P98 ( A Log P 98), the integrity of the Blood–Brain Barrier (BBB), the presence and influence of Cytochrome P4502D6 (CYP2D6), and the propensity for Hepatotoxicity (HEPATOX). 54–56…”
Section: Resultsmentioning
confidence: 99%
“…A multitude of parameters were computed, including the two-dimensional Fast Polar Surface Area (2D_FPSA), Atom-based Log P98 (A Log P98), the integrity of the Blood-Brain Barrier (BBB), the presence and influence of Cytochrome P4502D6 (CYP2D6), and the propensity for Hepatotoxicity (HEPATOX). [54][55][56] From Tables 2 and 3, it can be concluded that all the potent compounds displayed appropriate physicochemical properties and obeyed Lipinski's ''Rule of Five'' and ''Veber Rule'' and hence, they have drug-likeness and can be considered as probable A Log P = Ghose-Crippen-Viswanadhan octanol-water partition coefficient, M W = molecular weight, HBD = hydrogen bond donar, HBA = hydrogen bond acceptor, HT = hepatotoxic, HIA = human intestinal absorption, NI = non-inhibitor, NT = non-toxic. Solubility level: 0 (extremely low), 1 (very low), 2 (low), 3 (good), 4 (optimal), 5 (too soluble), 5 (molecules with one or more A Log P 98 types).…”
Section: Admet Predictionsmentioning
confidence: 99%
“…In silico methods have played a crucial role in identifying and optimizing potential small molecule inhibitors from var-ious sources, including marine-derived products, offering a rapid and cost-effective approach to drug development [80][81][82]. Marine natural products have garnered significant attention in drug discovery due to their structural diversity and bioactive properties.…”
Section: Discussionmentioning
confidence: 99%
“…Many recent studies have elucidated the 3D structures or the relevant homology models of several viruses, including SARS-CoV-2 [23][24][25][26]. This is part of the ongoing effort to expedite drug discovery when drug candidates can be identified based on such 3D-modeling approaches already available in the existing literature.…”
Section: D Structure Of the Walrus Calicivirus Capsid Protein Homolog...mentioning
confidence: 99%